Integrated nutrient management in summer barley ( Hordeum vulgare) in a cold desert of Himachal Pradesh - SHARMA, R P; SURI, V K; DATT, N (The Indian Journal of Agricultural Sciences, 2014)
A field experiment was Conducted during summer season of 1998 and 1999 to study the response of barley (Hordeum vulgare L., s.l.), to integrated use offannyard manure and fertilizer N in the cold desert soils of Himachal Pradesh. An application of N increased the grain (1 105 kg/ha) and straw yields (2265 kg/ha) significantly up to 75 kg N/ha in the absence of farmyard manure. However, the response was up to 60 kg N/ha when farmyard manure was also applied along with fertilizer N. The yield (1 659 kg/ha) obtained with 75 kg/ha alone was at par with that obtained with 60 kg N/ha along with farmyard manure @ 10 tonnes/ha. Yield-attributing characters, protein content and nutrient uptake supported the yield trends.